Enhanced Recovery after Planned Gynaecological Surgery: A Study on Gut Motility and Hospital Stay - Saleem, Uzma; Nadia Arif (Pakistan Armed Forces Medical Journal, 2024)
Objective: To evaluate the effectiveness of chewing gum in ameliorating post-operative ileus, reducing hospital stay and improving patient satisfaction after planned gynecological surgery. Study Design: Quasi-experimental study. Place and Duration of Study: Combined Military Hospital Kharian, Pakistan from Aug 2022 to Mar 2024. Methodology: The quasi-experimental study was conducted on a total of 400 patients satisfying the inclusion criteria. Patients were divided into two groups. Group-A had 243 patients while group-B had 157 patients. Patients in the group-A were made to start chewing gum 8 hours post surgery for 15 minutes thrice a day, whereas group-B did not chew any chewing gum. The outcome measures were time to first bowel sounds, passage of flatus, bowel opening, nausea, vomiting, abdominal distension, length of hospital stay and patient satisfaction. Results: Mean age of patients in groups A and B was 44.0 and 40.0 years respectively. The median time to first audible gut sounds and passage of flatus in group-A were 19.0(17.0-22.0) and 24.0(23.0-28.0) hours versus 23.0(21.0-24.0) and 28.0(27.0-28.5) hours in group-B, p≤0.001. Mean time of first liquid intake and bowel opening in group-A was 28.0(28.0-31.0) and 40.0(37.0-42.0) hours as opposed 31.0 (30.0-42.0) and 44.0(42.0-48.0) hours in group-B, p≤0.001. Mean length of hospital stay in group-A and B was 44.0(42.0-46.0) and 52.0(47.0-56.0) hours with a p-value ≤0.001. There was significantly less nausea and improved patient satisfaction in group-A. Conclusion: Gum chewing following surgery enhances post-operative Bowel function recovery, patient satisfaction and shortens hospital stay.